Magnetoresistive Effect and the Magnetic Parameters of Nanocrystalline Films Based on Co, Fe, Ag and Cu - V.B. Loboda; V.М. Коlomiets; Yu.О. Shkurdoda; V.А. Kravchenko; E.G. Kopanets (Журнал нано- та електронної фізики)
Here the results of the experimental studies of the magnetoresistive effect in three layer nano-crystalline magnetic films based on Co/Ag/Fe/S and Co/Cu/Fe/S are presented. The influence of the heat treatment on the value of their magnetoresistive rate is discussed. It is established that the maximum value of the effect is observed in the presence of ultrathin layer between the magnetic layers with comparable thicknesses.